2015
DOI: 10.1115/1.4030206
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Influence of Product Shape on Consumer Judgments Through Geometric Abstraction

Abstract: Understanding and tailoring the visual elements of a developing product to evoke desired perceived qualities and a positive response from the consumer is a key challenge in industrial design. To date, computational approaches to assist this process have either relied on stiff geometric representations, or focused on superficial features that exclude often elusive shape characteristics. In this work, we aim to study the relationship between product geometry and consumers' qualitative judgments through a visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…And based on these two, (3) how do we search for a good design? Challenges in answering these questions include high-dimensional or ill-defined design spaces such as for topologies [10,11], material microstructures [12,13,14], or complex geometries [15,16], expensive evaluations of designs and their sensitivities, e.g., due to model nonlinearity [17,18], coupled materials or physics [19,20,21], or subjective goodness measures [22,23], or search inefficiency due to the absence of sensitivities [24,25,26] or the existence of random variables [27].…”
Section: Related Workmentioning
confidence: 99%
“…And based on these two, (3) how do we search for a good design? Challenges in answering these questions include high-dimensional or ill-defined design spaces such as for topologies [10,11], material microstructures [12,13,14], or complex geometries [15,16], expensive evaluations of designs and their sensitivities, e.g., due to model nonlinearity [17,18], coupled materials or physics [19,20,21], or subjective goodness measures [22,23], or search inefficiency due to the absence of sensitivities [24,25,26] or the existence of random variables [27].…”
Section: Related Workmentioning
confidence: 99%
“…The stereotype they identified for each group had a distinct body shape and feature designs. Orbay et al [18] tested consumer judgments of cars' abstraction models and full models. They observed that subjects associated body shapes with certain unobservable attributes.…”
Section: Effects Of Body Shape and Features On Consumermentioning
confidence: 99%
“…Recent studies have shown that brand recognition is dependent on the fidelity of the design representation (Ranscombe et al 2012;Rasoulifar, Prudhomme & Eckert 2015). Informally, there is a level of realism to the design that must be achieved for customers to correctly identify vehicle brand (Orbay, Fu & Kara 2015). We build on this notion by representing vehicle designs using the highest fidelity representation possible whether a 2D image or a 3D high polygon mesh, as shown in Figures 1 and 2, respectively.…”
Section: D and 3d Representationsmentioning
confidence: 99%